1979
DOI: 10.1073/pnas.76.11.5669
|View full text |Cite
|
Sign up to set email alerts
|

Amplified dihydrofolate reductase genes in unstably methotrexate-resistant cells are associated with double minute chromosomes.

Abstract: Karyotype Analysis. Midlogarithmic phase cultures were treated with 0.06 ,ug of Colcemid per ml and metaphase spreads were prepared by a modification of the procedure of Deaven and Petersen (10). Cells were gently trypsinized, centrifuged at 800 X g, and resuspended with 0.5 ml of residual medium; 5 ml of 75 mM KCI (pH 7.0) at 37°C was added by drops and the mixture was incubated for 5-15 min at 370C. Cells were again pelleted and resuspended in 0.5 ml of residual medium; 4 ml of ice-cold methanol/acetic acid,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
143
0

Year Published

1982
1982
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(150 citation statements)
references
References 30 publications
7
143
0
Order By: Relevance
“…The amplified genes may be located within expanded regions on extended single chromosomes (9,32) or in small, mitotically paired, chromosomal elements called double minutes (18,26). Metaphase spreads of parental S3 and MTX-resistant S3-300 cells indicated that the resistant line had acquired large numbers of double minute chromosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The amplified genes may be located within expanded regions on extended single chromosomes (9,32) or in small, mitotically paired, chromosomal elements called double minutes (18,26). Metaphase spreads of parental S3 and MTX-resistant S3-300 cells indicated that the resistant line had acquired large numbers of double minute chromosomes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Cells grown in increasing concentrations of MTX developed resistance to the drug by overproducing its target enzyme, DHFR, as a result of amplification of the endogenous DHFR genes within the genome. In sta,ble transformants, the amplified DNA sequences usually reside in homogeneous staining regions of the chromosomes (11,34) some-like structures called double minutes (6,20). Subsequent studies showed that cloned DHFR genes and other genes cotransformed with them could also be amplified by this stepwise MTX selection when they were transferred into DHFR-deficient cells (10,21,22,32,35).…”
mentioning
confidence: 99%
“…The genetic stuctures responsible for this have been identified as the homogeneously staining regions (HSR), related to a stable methotrexate resistance. Double-minutes confer variable resistance as a function of their quantitative importance (Alt et al, 1978;Bostock et al, 1979;Kaufman et at., 1979). In addition to their theoretical interest, these results open interesting perspectives on the possible relationships between the cytogenetic examination of a tumour and its chemo-sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…can be related to cancer progression and also to cytostatic drug resistance (Bostock et al, 1979;Kaufman et al, 1979). Cytogenetics could thus become a useful, perhaps even an essential tool in the classification of digestive cancers (Yunis et al, 1981).…”
mentioning
confidence: 99%